Performance of coconut coir reinforced hydraulic cement mortar for surface plastering application - Sathiparan, N.; Rupasinghe, M.N.; Pavithra, B.H.M. (Elsevier, 2017)
This study was to investigate the effect of coconut coir on the strength and durability properties of cement-lime surface plaster mortar. The purpose of adding coconut coir into the mortar was due to coconut coir had a capacity in controlling cracking in the mortar. In this study, total 115 samples were prepared which were 100 cubes (150 mm 150 mm 150 mm) and 15 beam prisms (100 mm 100 mm 500 mm). Testing was included; water absorption, porosity, sorption rate for physical properties; acid attack resistance, alkaline attack resistance for durability properties; compression and flexural bending for strength properties. The samples were tested with mortar containing 0.125%, 0.25%, 0.50% and 0.75% of coconut coir. The percentage of coconut coir fraction was calculated based on the cement, lime, sand mix by mass. Test results show that, although compressive and flexural bending strength are not improving, but post crack properties such as ductility, residual strength, and toughness are increased with higher coconut coir fraction in the matrix.
Keywords: Masonry; Surface plaster